Clinical case severe course of coronavirus infection (COVID-19) in a child - Mateiko, H.B.; Matvisiv , M.V.; Pylyuk, I.I.; Nesterova , T.V.; Glushko, U.A. (Medicni Perspektivi, 2023)
A clinical case of a severe course of coronavirus infection (COVID-19) in an adolescent is described. A 15-year-old patient was admitted to the surgical department with suspicion of acute appendicitis. According to the results of the ultrasound examination of the abdomen it was decided to perform diagnostic laparoscopy, which excluded the presence of acute surgical pathology. The increase of intoxication symptoms and the data of epidemiological anamnesis, concerning the contact with patients with the catarrhal symptoms 3-4 weeks before the disease onset, were the reason for the examination for SARS-CoV-2. On the basis of a positive polymerase chain reaction for SARS-CoV-2 and existing pneumonia according to X-ray examination of the chest, the patient was transferred to an infectious disease hospital. Further examination revealed polyserositis (ascites, pleurisy); acute kidney damage (high levels of urea, creatinine, oliguria); cytolytic syndrome (increased level of aspartate aminotransferase in 1,7 times); high level of C-reactive protein and increased level of procalcitonin, which corresponded to the local infection. After the administration of the first dose of intravenous immunoglobulin the patient’s condition has improved significantly. The set of symptoms of multiple organ damage in this clinical case provides grounds for differential diagnosis between coronavirus disease and multisystem inflammatory syndrome in children on the background of the coronavirus infection COVID-19. Based on the diagnostic criteria for multisystem inflammatory syndrome in children presented by the World Health Organization, the Centers for Disease Control and Prevention, the British Medical Journal, the American Academy of Pediatrics, this clinical case can be considered as multisystem inflammatory syndrome.